Utilização do bagaço do mosto da cerveja para desenvolvimento de pão de forma fermentado com diferentes bactérias lácticas - Castro, Camila Gomes Godinho de (2013)
Bread is a food consumed in various peoples and cultures, appreciated by the population being considered as an important source of nutrients. Because of these characteristics several studies have being conducted in order to improve its processing and the use of new materials for partial or total replacement of the wheat flour. The brewing industry generates tons of wet residue per year, such waste is typically used for animal feed production. The aim of this study was to develop a bun with partial replacement of wheat flour by flour mash beer, fermented with lactic acid bacteria. The flour beer wort (G1), wheat flour (H1), and mixed flour (AM5) 60:40, were evaluated for physico-chemical, nutritional and rheological properties. For the fermentation of the dough breads were used lactic acid bacteria Lactobacillus sakei (A1), Lactobacillus plantarum (B1), Lactobacillus amylophilus (C1), Lactobacillus amylovorus (D1), a mixture of lactic acid bacteria (E1) combined with dry yeast and a bread dough containing yeast only (F1). The flour beer wort showed low levels of moisture and carbohydrates, increased rates of ash, fiber, lipids, and also showed dark coloration when compared to other cereal flours. The mixed flour presented a reduced quality technology, which was confirmed by the specific volume of the bread and the results found in farinogram, alveogram, and falling number. When wheat flour was replaced by flour mixed in bread production, it was observed an increase in moisture, ash, fiber and lipids, and a decrease in the amount of carbohydrates and proteins. The breads fermented with lactic acid bacteria did not increase the availability of fiber content, protein and moisture, however the content of ash increased in those breads produced by lactic acid bacteria Lactobacillus sakei (A1) and Lactobacillus plantarum (B1). The lactic acid bacteria yielded an increase in the availability of carbohydrates and lipids. This study has showed that a partial replacement of wheat flour by flour beer wort has a potential for development of new products for human consumption, since the results obtained by the action of lactic acid bacteria produced breads with a nutritional profile compatible for consumption human.